Experiences of patient education among people affected by cardiovascular disease: a qualitative study based on Andragogy model - Negin Niksadat; Mohtasham Ghaffari; Ali Ramezankhani; Sakineh Rakhshanderou; Ali Vasheghani Farahani; Reza Negarandeh (BMC, 2023)
Abstract Background Patient education is a key component of patient care, positively affecting health promotion and self-care ability. In this regard, an extensive body of research supports the use of the andragogy model in patient education. The study aimed to explore the experiences of people with cardiovascular disease in patient education. Methods This qualitative study involved 30 adult patients with cardiovascular disease who were hospitalized or had a history of hospitalization. They were purposively recruited with maximum variation from two large hospitals in Tehran, Iran. Data were gathered by conducting semi-structured interviews. Data collection was done by conducting semi-structured interviews. Then, the data were analyzed using directed content analysis and a preliminary framework based on six constructs of the andragogy model. Results Data analysis resulted in the development of 850 primary codes, which were reduced to 660 during data reduction. These codes were grouped into nineteen subcategories under the six primary constructs of the andragogy model, i.e., need-to-know, self-concept, prior experience, readiness for learning, orientation to learning, and motivation for learning. The most common problems in patient education were associated with self-concept, previous experience, and readiness for learning components. Conclusion This study provides valuable information about the problems of patient education for adults with cardiovascular disease. Correction of the issues identified can improve care quality and patient outcomes.